Global Integration of Central and Eastern European Financial Markets – The Role of Economic Sentiments - Ansgar Belke; Joscha Beckmann; Michael Kühl (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
This paper examines the importance of different economic sentiments, e.g. consumer moods, for the Central and Eastern European countries (CEECs) during the transition process. We first analyze the importance of economic confidence with respect to the CEECs' fi nancial markets. Since the integration of formerly strongly-regulated markets into global markets can also lead to an increase in the dependence of the CEECs' domestic market performance on global sentiments, we also investigate the relationship between global economic sentiments and domestic income and share prices. Finally, we test whether the impact of global sentiments and stock prices on domestic variables increases proportionally with the degree of integration. We also account for eff ects stemming from global income. For these purposes, we apply a restricted cointegrating VAR (CVAR) framework based upon a restricted autoregressive model which allows us to distinguish between the long-run and the short-run dynamics. For the long run we find evidence supporting relationships between sentiments, income and share prices in the case of the Czech Republic. Our results for the short run suggest that economic sentiments in general are influenced by share prices but also off er some predictive power with respect to the latter. What is more, European sentiments play an important role in particular for the CEECs' share prices and income. The significance of this link increases with economic integration. – – Das Papier untersucht die Rolle von wirtschaftlichen Stimmungen bei der Transformation der mittel- und osteuropäischen Länder, z.B. im Hinblick auf die Finanzmärkte, sowie den Zusammenhang zwischen globalen wirtschaftlichen Stimmungen, Einkommen und Aktienkursen. Das zentrale Ergebnis: Stimmungen haben einen Einfluss auf die Entwicklung der Aktienkurse und des Einkommens in Mittel- und Osteuropa. Hinsichtlich der Aktienkurse nimmt der Einfluss der globalen Sentiments mit fortschreitender Integration sogar teils zu. Auch der Einfluss des globalen Einkommens steigt. Insgesamt deuten die Ergebnisse sowohl auf einen realen Konvergenzprozess als auch auf eine Integration der osteuropäischen Finanzmärkte in die globalen Märkte hin. Es kann außerdem gefolgert werden, dass Marktstimmungen bis zu einem gewissen Maß Einkommensprognosen erlauben.
Keywords: E44; G15; P2; 330; Cointegration; European integration; financial markets; restricted autoregressive model; sentiments; Finanzmarkt; Marktintegration; Europäische Integration; Konsumklima; Geschäftsklima; Börsenkurs; Volkseinkommen; Kointegration; Schätzung; EU-Staaten (Osteuropa); Tschechische Republik